Antigen detection as a point-of-care test for TB: the case of lipoarabinomannan. (May 2012) - Swaminathan, Soumya; Rekha, VV Banu
Evaluation of: Lawn SD, Kerkhoff AD, Vogt M, Wood R. Diagnostic accuracy of a low-cost, urine antigen, point-of-care screening assay for HIV-associated pulmonary tuberculosis before antiretroviral therapy: a descriptive study. Lancet Infect. Dis. 12(3), 201–209 (2011). The limitations of sputum smear microscopy, routine chest radiology for HIV-associated TB and culture-based diagnosis are well recognized, especially in resource-limited settings. The diagnostic accuracy of a new point-of-care lateral-flow urine strip test for lipoarabinomannan (Determine ® TB-LAM; Alere, MA, USA), which costs US$3.50 per test strip and provides results within 30 min, was evaluated in a cohort of South African patients for HIV-associated TB before starting anti-retroviral therapy in South Africa. Prevalence of culture-positive TB cases was 17.4%, among which 28.2% had sputum smear positivity. Determine ® TB-LAM (Alere, MA, USA) had highest sensitivity at low CD4 cell counts: 66.7, 51.7 and 39.0% at <50 cells, <100 cells and <200 cells per µl, respectively; specificity was greater than 98% for all strata. There was an incremental sensitivity when Determine TB-LAM was combined with smear microscopy, which did not differ statistically from the sensitivities obtained by testing a single sputum sample with the Xpert ® MTB/RIF (Cepheid; CA, USA) assay. Determine TB-LAM is a simple, low-cost alternative to existing diagnostic assays for TB screening in HIV-infected patients with very low CD4 + cell counts.